Применение психологических теорий обучения при дистанционном образовании - Шубин, И. Ю.; Выродов, А. П.; Мирошникова, О. H.; Сладков, A. B. (УАДО, 2002)
The paper deals with application of learning theories to distance education. The barest necessity of such application is proved. The basic concepts of several modern learning theories are given. The paper outlines some of the environmental pedagogical dimensions. The recommendations of learning theory application to distance education are made. It is pointed out, that a creation of scenario of computer based learning system must be concerned with learning theories set
Keywords: дистанционное образование; психологические теории обучения